Mathematics in transport : selected proceedings of the 4th IMA International Conference on Mathematics in Transport : in honour of Richard Allsop /: selected proceedings of the 4th IMA International Conference on Mathematics in Transport : in honour of Richard Allsop. (2007) - Unknown
No abstract available